On the Viability of Catalytic Turnover via Al−O/B−H Metathesis: The Reactivity of β‐Diketiminate Aluminium Hydrides towards CO2 and Boranes. Issue 51 (17th August 2018) - Caise, Alexa; Jones, Dafydd; Kolychev, Eugene L.; Hicks, Jamie; Goicoechea, Jose M.; Aldridge, Simon
Abstract: A series of β‐diketiminate stabilized aluminium hydrides of the type (Nacnac)Al(R)H has been synthesized offering variation in the auxiliary R substituent and in the Nacnac backbone. These show significant variation in the nature of the Al−H bond: electron‐donating R groups give rise to weaker (and presumably more hydridic) Al−H bonds, leading to enhanced rates of reactivity towards CO2 . The resulting κ 1 ‐formate complexes (Nacnac)Al(R){OC(O)H} have been isolated and their reactivity towards B−H‐containing reductants probed. In the case of HBpin no reaction is observed (even under forcing conditions), while the more reactive boranes HBcat and {H(9‐BBN)}2 ultimately yield boryloxy complexes of the type (Nacnac)Al(R)(OBX2 ) (X2 =cat, 9‐BBN). However, no hint of Al−O/B−H metathesis is observed even under forcing conditions. With BH3 ⋅ SMe2 the major product is a related boryloxy system, although (uniquely) in this case a minor product is observed which contains an Al−H bond. We hypothesize that (Nacnac)Al(R)(κ 2 ‐BH4 ) is formed (despite the unfavourable thermodynamics of Al−O/B−H metathesis) due to the additional driving force provided by coordination of the strongly Lewis acidic BH3 unit to the Al−H bond. That said, we find that (unlike the analogous gallium systems) no catalytic turnover can be achieved in the reduction of CO2 by boranes mediated by these aluminium hydrides. Abstract : Al‐O, Al‐O, Al‐O : Mononuclear β‐diketiminate stabilized hydrides have recently been implicated in a number of reduction processes of C=O bonds. Here we show that turnover in the borane reduction of CO2 by a range of such complexes is rendered thermodynamically non‐viable by the excessive strength of the Al−O bond.